Geotechnical Aspects of Underground Construction in Soft Ground 2014
DOI: 10.1201/b17240-37
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel modelling: Stress release and constitutive aspects

Abstract: Tunnel construction in soft ground has evolved significantly over the last 20 years, especially on the matter of settlement control. This was achieved by guiding the TBM operation to control the main factors that induced soil displacements, like the face pressure and the soil-lining void closure. However, the design methods and numerical modeling procedures where not adapted to these new conditions, sometimes applying boundary conditions, constitutive parameters or state variables with no physical meaning to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…The increase in the stiffness (mainly for K 0 <1), and the initial mean stress (more significantly for K 0 <1) results in a lesser surface volume loss. This is consistent with the findings of Dias and Bezuijen . They pointed out that for the isotropic state ( K 0 =1), the variation of stress is dominated by the stress in the deviatoric direction during tunneling process.…”
Section: Influence Of Important Factors On the Tunneling Induced Grousupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in the stiffness (mainly for K 0 <1), and the initial mean stress (more significantly for K 0 <1) results in a lesser surface volume loss. This is consistent with the findings of Dias and Bezuijen . They pointed out that for the isotropic state ( K 0 =1), the variation of stress is dominated by the stress in the deviatoric direction during tunneling process.…”
Section: Influence Of Important Factors On the Tunneling Induced Grousupporting
confidence: 92%
“…This is consistent with the findings of Dias and Bezuijen. 49 They pointed out that for the isotropic state (K 0 =1), the variation of stress is dominated by the stress in the deviatoric direction during tunneling process. For the other states, the responses are distinguishable on whether the vertical stress is the initial major ( 1 ) or minor ( 3 ) principle stress where the normal stress to the tunnel is 3 at tunnel crown for high value of K 0 and at tunnel side for low value of K 0 .…”
Section: Effect Of Kmentioning
confidence: 99%
“…where w is the width of the mesh, D is the diameter of the tunnel, and H is the height from the ground surface to the [25]) and eld measurement (Möller and Vermeer [26]). e boundary conditions are selected as viscous for the lateral boundaries, while the top boundary is taken as free as has been proposed in the literature to accurately capture the deformation phenomena.…”
Section: Mesh Dimensions and Boundary Conditionsmentioning
confidence: 99%
“…In particular, the use of such a constitutive model produces a more realistic ground settlement profile and leads to a surface settlement trough which better represents the observed data. [10] showed that the surface settlements and their relation to the volume losses measured on the tunnel boundary were significantly different among different models, especially between the models with linear and non-linear stress-strain relations.…”
mentioning
confidence: 98%